Interpersonal Communication-Based Religious Services: Assisting Elderly Hajj Pilgrims in Medan - Alya Rahmayani Siregar; Mailin Mailin; Lahmuddin Lahmuddin (Journal of General Education and Humanities, 2026)
The increasing number of elderly Hajj pilgrims in Medan City presents specific challenges in religious services, particularly related to physical decline, communication barriers, and the need for emotional support. These conditions often affect the quality of worship experiences among elderly pilgrims. This study aims to analyze the role of interpersonal communication in religious services for elderly Hajj pilgrims and to formulate an effective communication model that ensures a safe, comfortable, and meaningful worship experience. This research employs a qualitative approach, with field research and descriptive analysis. Data were collected through in-depth interviews, non-participant observations, and documentation involving companions, elderly members of the Hajj Guidance Group (KBIH), administrators, health workers, and pilgrims’ families. Data validity was ensured through triangulation and member checking techniques. The results indicate that interpersonal communication plays a strategic role as a medium for empathy, adaptation, and problem-solving in assisting elderly pilgrims. An effective communication model is characterized by patience, empathy, simple, clear language, two-way communication, and active family involvement. Companions adapt their communication styles to the physical and psychological conditions of the elderly; health workers use visual and nonverbal communication to enhance understanding; and families support the communication process through regular meetings and digital platforms such as WhatsApp. This communication model significantly improves the quality of religious services and worship experiences for elderly Hajj pilgrims.